Experimental Study on Fire Resistance of Phase Change Energy Storage Concrete Partition Walls - Meichun Zhu; Jiangang Li; Ying Wang; Fanqin Meng (Fire)
Phase change material (PCM) concrete walls represent a new type of energy storage wall. It is of great significance to study the fire resistance of PCM concrete walls to ensure the safety of these kinds of components in service. For this reason, fire resistance tests on eight PCM concrete partition wall specimens under the conditions of the ISO-834 standard fire curve were carried out. The tested wall structures included a solid wall and a double-layer wall with an air gap. The PCM used was paraffin phase change microcapsules, which were replaced with a fine aggregate according to the principle of equal volumes, at replacement proportions of 0%, 7%, 10%, and 14%. The test results showed that explosive spalling of the PCM concrete occurred when the double-layer wall specimen with a 10% replacement proportion was heated for 31 min, and the other seven specimens met the integrity requirements after heating for 90 min. The 100 mm thick ordinary concrete solid partition wall specimen did not meet the thermal insulation requirements after 90 min. The addition of PCM and the use of a double-layer structure with an air gap can both improve the wall’s thermal insulation performance; however, it is not the case that, the greater the amount of PCM used, the better the thermal insulation performance of the wall. The reasons that the PCM concrete spalled in the double-layer wall specimen with a 10% replacement proportion are discussed. This study provides critical insights into optimizing the PCM content and wall design for fire-safe energy-efficient buildings, offering practical guidance for sustainable construction practices.